Revised Trauma Score (RTS) as a Mortality Predictor on Abdominal Trauma - Legiran; Ade Dian Anggraini; Efman EU Manawan (Sriwijaya Journal of Surgery, 2018)
Introduction: Trauma is a major health problem throughout the world. Trauma is the most common cause of death and the most common cause of disability in adults and young adults. Abdominal trauma accounts for 7-10% of all trauma sufferers and causes severe trauma. The purpose of this study was to determine the relationship between the Revised Trauma Score (RTS) to the mortality of abdominal trauma sufferers. Methods: This study was an observational analytic study with a retrospective design to assess the relationship between Revised Trauma Score (RTS) and mortality in abdominal trauma patients treated in the Emergency Department of RSUP DR. Mohammad Hoesin Palembang. Data collected were analyzed using SPSS-23 devices using the chi-square method and Mann Whitney Results: 144 abdominal trauma patients studied. The mean age was 28 ± 11,340 years, 97.4% were male, 64.0% of patients had abdominal trauma. The average RTS value was 7.429 ± 1,001. The mean value in the group of patients who died was 6.628 ± 0.795 and the mean value of the RTS in the group of patients who did not die was 7.459 ± 0.795. There was a significant relationship between RTS values ​​and mortality in abdominal trauma patients (p = 0.0.03). Conclusion: the results of this study indicate that RTS is a meaningful assessment system in predicting death in abdominal trauma patients